Preparation method of coal gangue ceramsite concrete coated with ash on surface
By wrapping the surface of the coal gangue ceratops to form a silicate shell, the concrete performance problem caused by the high water absorption rate of the ceratops is solved, and the effect of improving the performance and mechanical properties of concrete mixture is achieved.
Patent Information
- Application Number
- CN202411820009.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
AI Technical Summary
Due to the high water absorption rate of gangue ceramic concrete, the slump loss of concrete mixture is too large, affecting pumping and casting. Pre-wetting treatment will reduce the cylinder pressure strength and concrete strength of the ceramic.
By using composite gelling materials in the granulator to wrap the surface of the coal gangue ceramic granules, a silicate shell of about 1 mm is formed to reduce the water absorption rate of the ceramic granules.
It reduces the water absorption rate of coal gangue ceratops, improves the mixing performance and mechanical properties of concrete, enhances the anti-freeze-thaw performance, and is suitable for a variety of engineering fields.
Smart Images

Figure CN119661131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete preparation, and in particular to a method for preparing surface-coated ash-coated coal gangue ceramsite concrete. Background Art
[0002] As a solid waste, coal gangue has clay properties because it contains a large amount of silicon dioxide, iron oxide and aluminum oxide. About 40% of it can be burned into coal gangue ceramsite, which can be added to concrete as a lightweight aggregate to prepare an apparent density of less than 1950kg / m 3 Gangue ceramsite lightweight aggregate concrete. Gangue ceramsite is a loose porous material. When used as lightweight aggregate, it has a large water absorption capacity. Under the condition of the same working performance, it requires a higher water-cement ratio than ordinary concrete. The water absorption process of lightweight aggregate is most intense within the last 10 to 15 minutes of concrete mixture preparation, and the amount of water absorption depends on the water-cement ratio of the concrete mixture. The larger the water-cement ratio of the concrete mixture, the greater the amount of water absorbed by the lightweight aggregate from the mixture. However, this is not conducive to the application of lightweight aggregate concrete, because fluid concrete and premixed concrete technology are currently widely used. Fluid lightweight aggregate concrete may cause excessive slump loss of concrete mixture due to its high water absorption rate, affecting pumping and pouring, and segregation of concrete mixture due to improper construction treatment such as long-distance transportation, excessive self-fall height during pouring, and long vibration time.
[0003] At present, pre-wetting treatment is mainly used in engineering applications to reduce the problems caused by excessive water absorption of ceramsite.
[0004] For example, in Li Mengjuan. Study on the influence of ceramsite properties and pretreatment on the performance of ceramsite concrete [J]. Northern Architecture, 2024, 9(03): 104-108, it is believed that prewetting is more effective in solving the problem, but the cylinder compressive strength of lightweight aggregate that has been prewetted will be significantly reduced, so that the strength of the prepared concrete will also be significantly reduced and the dispersion is larger. If the concrete is mixed with the total water content during use, a large amount of water will be added at one time when high fluidity is required, which will inevitably cause stratification and segregation of the freshly mixed concrete. Therefore, any method and way to reduce the water absorption rate of lightweight aggregate will be conducive to the expansion of the application range of lightweight aggregate concrete and the improvement of its performance. Summary of the invention
[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a preparation method of surface-coated coal gangue ceramsite concrete, which uses cement and mineral admixtures to coat ceramsite in a granulator, coats the surface of the ceramsite with a layer of composite cementitious material, and forms a layer of silicate shell of about 1 mm on the surface of the ceramsite through the hydration of the cementitious material. Thereby reducing the water absorption rate of coal gangue ceramsite, the method has the characteristics of simple operation and easy implementation and promotion.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing surface-coated coal gangue ceramsite concrete comprises the following steps:
[0008] Step 1: Prepare composite cementitious materials with cement, fly ash or mineral powder and silica fume, and stir them with a mixer until they are evenly mixed;
[0009] Step 2: quantitatively weigh the composite cementitious material and coal gangue ceramsite obtained in step 1;
[0010] Step 3: Pour the ceramsite weighed in step 3 into a granulator, start the granulator, add the composite gelling material weighed in step 2 three times, and use a spray pot to spray 1 / 3 of the total water consumption on the ceramsite each time the composite gelling material is added to obtain ceramsite after ash coating;
[0011] Step 4: curing the ceramsite after the ash coating treatment;
[0012] Step 5: Use the ash-coated coal gangue expanded clay to completely replace the coarse aggregate to prepare coal gangue expanded clay concrete.
[0013] In step 1, the cement used is ordinary Portland cement, the fly ash is Class II fly ash, and the silica fume is SF96 silica fume; the composite cementitious material is prepared according to the ratio of 6 to 8 parts of cement, 1 to 3 parts of fly ash or mineral powder, and 1 part of silica fume, and stirred for 2 to 3 minutes using a mixer.
[0014] In the step 2, the mixture is prepared in a ratio of 1 part of the composite cementitious material to 1.5 to 4.5 parts of the coal gangue ceramsite.
[0015] In step 3, the rotation speed of the granulator used is 25 r / min, and the maximum mass of ceramsite that can be processed each time is 2.4 kg, wherein the total water consumption is calculated based on 50 g of water per 1 kg of ceramsite.
[0016] In step 4, the mixture is placed in a standard curing room with a temperature of 20±2° C. and a humidity of more than 95% for 3 days of curing.
[0017] In the step 5, the LC30 gangue ceramsite concrete is prepared by mixing the gangue ceramsite, cement, fly ash and fine aggregate after ash coating treatment;
[0018] In the step 5, the ash-coated coal gangue ceramsite concrete material includes the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of coal gangue ceramsite treated by ash-coated impregnation, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer;
[0019] The compressive strength of the cube of the ash-coated coal gangue ceramsite concrete meets the strength design requirement of LC30 lightweight aggregate concrete.
[0020] The preparation of coal gangue ceramsite concrete comprises the following steps: mixing surface-coated ceramsite, natural river sand, cement, fly ash and water reducing agent according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface-coated ceramsite concrete;
[0021] The vibration time of the surface coated ceramsite concrete during molding should not exceed 5s.
[0022] Surface-coated coal gangue ceramsite concrete has CSH gel on the ash coating layer of coal gangue ceramsite. The ash coating layer in the interface transition zone between the ceramsite and the cement matrix provides a "gradient transition" mechanical structure, avoiding the existence of a weak interface transition zone (ITZ); a silicate shell of about 1 mm is formed after the surface is coated with ash, and the silicate shell moderately reduces and evens out the water absorption rate of the ceramsite, avoiding the problem of uneven local water-cement ratio of concrete caused by differences in water absorption capacity of different ceramsites, and improving the consistency of concrete performance; in the process of concrete hardening, the water absorbed by the ceramsite in the mixing stage is gradually released through some capillary pores on the surface, alleviating the self-shrinkage phenomenon inside the matrix, promoting cement hydration and secondary reactions of admixtures, and enhancing the strength of the matrix.
[0023] The surface-coated coal gangue ceramsite concrete is suitable for various engineering fields;
[0024] In building structures, it is used in high-rise buildings, bridge components and prefabricated components;
[0025] In infrastructure, it is used in roadbeds, culvert pipes and retaining walls;
[0026] In marine engineering, it is used in docks and wave-breaking walls;
[0027] In industrial buildings, it is used for wear-resistant floors and anti-corrosion components in chemical plants.
[0028] Beneficial effects of the present invention:
[0029] After the composite cementitious material is used to coat the surface of the ceramsite, the ceramsite coated with the composite cementitious material has a smoother surface, which can reduce the friction between the ceramsite and the cement slurry, enhance the fluidity and pumpability of the mixture, increase the surface hardness and rigidity of the ceramsite, and further enhance its mechanical properties through the bonding between the composite cementitious material on the surface and the concrete slurry.
[0030] The present invention can reduce the water absorption rate of coal gangue ceramsite, thereby improving the mixing performance of coal gangue ceramsite concrete. Compared with ceramsite concrete prepared with untreated ceramsite and pre-wetted ceramsite, the cube compressive strength and splitting tensile strength of coal gangue ceramsite concrete after ash coating treatment are both better, and the pore moisture content of ceramsite after water absorption is reduced, thereby reducing the internal expansion pressure in the freeze-thaw cycle and enhancing the anti-freeze-thaw performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the appearance morphology of coal gangue expanded clay before and after ash coating treatment.
[0032] Figure 2 This is a trend chart showing the effect of fly ash content in composite cementitious materials on the 24h water absorption rate of fly ash coated expanded clay.
[0033] Figure 3 This is a trend chart showing the effect of the amount of mineral powder added in the composite cementitious material on the 24h water absorption rate of the lime-coated expanded clay.
[0034] Figure 4 This is a trend chart showing the effect of different lime-coated expanded clay on the compressive and splitting tensile strength of concrete.
[0035] Figure 5 This is the appearance morphology of coal gangue ceramsite concrete after 100 rapid freeze-thaw cycles. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0037] A method for preparing surface-coated coal gangue ceramsite concrete comprises the following steps:
[0038] Step 1: Prepare a composite cementitious material according to the ratio of 6 to 8 parts of cement, 1 to 3 parts of fly ash or mineral powder, and 1 part of silica fume, and stir it with a mixer for 2 minutes;
[0039] Step 2: quantitatively weigh the composite cementitious material and coal gangue ceramsite obtained in step 1 according to the ratio of 1 part ash to 1.5 to 4.5 parts coal gangue ceramsite;
[0040] Step 3: Pour the ceramsite weighed in step 3 into the granulator, start the granulator, add the composite cementitious material weighed in step 2 three times, and use a spray pot to spray 1 / 3 of the total water consumption on the ceramsite each time the ash is added, wherein the total water consumption is calculated based on 50 grams of water per kilogram of ceramsite;
[0041] Step 4: Place the ceramsite after ash coating in a standard curing room with a temperature of 20±2℃ and a humidity of more than 95% for 3 days;
[0042] Step 5: Use the ash-coated coal gangue expanded clay to completely replace the coarse aggregate to prepare coal gangue expanded clay concrete.
[0043] In the step 1, the cement used is ordinary Portland cement, the fly ash is Class II fly ash, and the silica fume is SF96 silica fume.
[0044] In step 2, the physical properties of the gangue ceramsite are a particle size of 5 to 16 mm and a bulk density of 900 to 950 kg / m 3 , apparent density 1300~1330kg / m 3 , 1h water absorption rate 6.0%~6.5%, cylinder pressure strength 5.0~6.0MPa.
[0045] In step 3, the rotation speed of the granulator used is 25 r / min, and the maximum mass of ceramsite that can be processed each time is 2.4 kg, wherein the total water consumption is calculated based on 50 g of water per 1 kg of ceramsite.
[0046] In step 4, the water absorption rate of the lime-coated ceramsite after standard curing for 3 days is tested, and the test is performed with reference to the light aggregate water absorption rate test method specified in the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method", and the test steps are as follows:
[0047] (1) Take 1 kg of sample and sieve it through a sieve with a mesh size of 2.36 mm. Dry the residue to a constant weight.
[0048] (2) Mix the sample evenly, divide it into three parts, weigh them separately, and then put them into a container filled with water. Press the floating particles into the water. The sample is immersed in water for 1 to 24 hours.
[0049] (3) Take the sample out of the container at 1 h, 3 h, 6 h, and 24 h, drain the water for 1 min to 2 min, then pour it on a wrung wet towel. Hold the two ends of the towel with your hands to make it into a groove shape. Let the ceramsite roll back and forth on the towel 8 to 10 times, then pour it into an enamel dish to make it saturated and dry. Weigh it and calculate its water absorption rate.
[0050] (4) The water absorption rate is calculated according to formula (1):
[0051]
[0052] Where:
[0053] ω a ——Water absorption rate of ceramsite after 1h, 3h, 6h and 24h, %;
[0054] m0——mass of the immersed sample, in grams (g);
[0055] m1——mass of dried sample, in grams (g);
[0056] The arithmetic mean of three measured values was taken as the test result.
[0057] In step 5, LC30 gangue ceramsite concrete is prepared by mixing gangue ceramsite with surface ash treatment, cement, fly ash and fine aggregate. The cement is P·O42.5 produced by Shaanxi Conch Cement Company, which complies with the national standard GB175-2023. The fly ash is Class II ash, which complies with the national standard GB 1596-2017. The fine aggregate is natural river sand with a fineness modulus of 2.7 and an apparent density of 2650kg / m 3 , belonging to zone II sand. The admixture is C1029 polycarboxylate water reducer produced by Fuke, with a water reduction rate of 30%.
[0058] In step 5, the gangue ceramsite concrete material includes the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of gangue ceramsite treated by ash coating and impregnation, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer.
[0059] The compressive strength of the coal gangue ceramsite concrete cube meets the strength design requirements of LC30 lightweight aggregate concrete.
[0060] The preparation of coal gangue ceramsite concrete comprises the following steps: mixing surface-coated ceramsite, natural river sand, cementitious material and water reducing agent according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface-coated ceramsite concrete;
[0061] The surface coated ceramsite concrete should not be vibrated for more than 5 seconds during molding. Figure 1 .
[0062] The surface coated ceramsite concrete features include:
[0063] Improved performance of the mixture: The ceramsite coated with composite cementitious materials has a smoother surface, which can reduce the friction between the ceramsite and cement paste, enhance the fluidity and pumpability of the mixture, and increase the slump by 18% to 27% compared with ordinary ceramsite concrete. After the ceramsite is coated with cement, the water absorption rate of the ceramsite is reduced by 20 to 30% within 1 hour, and the water content in the concrete is more evenly distributed, thereby reducing the risk of bleeding and segregation.
[0064] Improved mechanical properties: The ash coating increases the surface hardness and rigidity of expanded clay, and the 28d compressive strength of concrete is increased by 15% to 32%. The bonding strength between the composite cementitious material on its surface and the concrete paste is significantly improved, thereby increasing the 28d splitting tensile strength of concrete by 10% to 30%.
[0065] Improved frost resistance and durability: The lime coating treatment reduces the pore moisture content of expanded clay after absorbing water, thereby reducing the internal expansion pressure during the freeze-thaw cycle and enhancing the freeze-thaw resistance. The relative dynamic elastic modulus and mass loss after 100 freeze-thaw cycles are improved compared with ordinary expanded clay concrete.
[0066] Embodiment 1:
[0067] Prepare 3 parts of about 2kg of composite cementitious materials, the proportions of which are 8 parts of cement, 1 part of fly ash, and 1 part of silica fume; 7 parts of cement, 2 parts of fly ash, and 1 part of silica fume; 6 parts of cement, 3 parts of fly ash, and 1 part of silica fume. Each part of composite cementitious material is stirred for 2 minutes using a mortar mixer. Weigh 9 parts of about 1kg of coal gangue ceramsite, and then divide the prepared 3 parts of composite cementitious materials into 3 parts according to the mass ratio of ceramsite to ash of 1.5, 3, and 4.5, respectively, to finally obtain 9 parts of composite cementitious materials. When wrapping the ash, first place the ceramsite in the granulator, start the granulator, and add the composite cementitious materials weighed in step 2 three times. Each time the ash is added, use a spray pot to spray 1 / 3 of the total water consumption on the ceramsite in batches. The total water consumption is calculated as 50g of water per 1kg of ceramsite. After the ash coating is completed, the gangue ceramsite is placed in a standard curing room with a temperature of 20±2℃ and a humidity of more than 95% for 3 days. After that, the water absorption rate test is carried out. 9 parts of the gangue ceramsite after ash coating are completely immersed in water, and taken out after 1h, 3h, 6h, and 24h respectively. According to the water absorption rate test method in the national standard, it is made into saturated surface dry weight, and its water absorption rate is calculated, such as Figure 2 .Depend on Figure 2 (a) It can be seen that as the clay-lime ratio increases, the water absorption rate of ceramsite decreases significantly. Among them, the clay-lime ratio of 4.5 has the best effect. Compared with the clay-lime ratio of 1.5, the water absorption rate of ceramsite coated with ceramsite in 1 hour decreases by 24%, and the water absorption rate in 24 hours decreases by 13%. Figure 2 (a), (b), (c) It can be seen that when the ratio of composite cementitious materials is 7:2:1, the water absorption rate of ceramsite treated with ash is the smallest and the effect is the best.
[0068] This is because when the mixed ash ratio is 7:2:1, the three materials work together in the microstructure, forming a dense and uniform ash coating through cement hydration reaction, fly ash pozzolanic reaction and particle size filling effect. When the fly ash ratio is 20%, its filling effect and reaction activity are balanced, which does not affect the initial gelling effect of cement and can give full play to the later densification effect. This ratio ensures that the ash coating has sufficient strength support, high density and low porosity, thereby minimizing the water absorption rate of ceramsite.
[0069] Embodiment 2:
[0070] Prepare 3 parts of about 2kg of composite cementitious materials, the proportions of which are 8 parts of cement, 1 part of mineral powder, and 1 part of silica fume; 7 parts of cement, 2 parts of mineral powder, and 1 part of silica fume; 6 parts of cement, 3 parts of mineral powder, and 1 part of silica fume. Each part of composite cementitious material is stirred for 2 minutes using a mortar mixer. Weigh 9 parts of about 1kg of coal gangue ceramsite, and then divide the prepared 3 parts of composite cementitious materials into 3 parts according to the mass ratio of ceramsite to ash of 1.5, 3, and 4.5, respectively, to finally obtain 9 parts of composite cementitious materials. When wrapping the ash, first place the ceramsite in the granulator, start the granulator, and add the composite cementitious materials weighed in step 2 three times. Each time the ash is added, use a spray pot to spray 1 / 3 of the total water consumption on the ceramsite in batches. The total water consumption is calculated as 50g of water per 1kg of ceramsite. After the ash coating is completed, the gangue ceramsite is placed in a standard curing room with a temperature of 20±2℃ and a humidity of more than 95% for 3 days. After that, the water absorption rate test is carried out. 9 parts of the gangue ceramsite after ash coating are completely immersed in water, and taken out after 1h, 3h, 6h, and 24h respectively. According to the water absorption rate test method in the national standard, it is made into saturated surface dry weight, and its water absorption rate is calculated, such as Figure 3 .Depend on Figure 3 It can be seen that with the increase of the clay-lime ratio, the water absorption rate of the ceramsite decreases significantly. When the ratio of composite cementitious materials is 6:3:1 and the clay-lime ratio is 4.5, the ceramsite obtained by ash coating treatment has the lowest water absorption rate in 24 hours, and its water absorption rate in 1 hour can reach 4.1%.
[0071] Embodiment 3:
[0072] Untreated ceramsite, 1h pre-wetted ceramsite, and examples 1 and 2 were used to change the fly ash and mineral powder dosage respectively. The ceramsite obtained by ceramsite-ash ratio 4.5 completely replaced the coarse aggregate to prepare ceramsite concrete, and the concrete slump and expansion test were carried out. The concrete mix proportion and mixture performance are shown in Table 1. It can be seen that the ceramsite concrete prepared by using ceramsite coated with ash has better working performance than untreated ceramsite as a whole. The different proportions of fly ash and mineral powder in the composite cementitious material during ash coating also have a certain impact on the working performance of concrete. The slump and slump expansion of the control group (Blank) using untreated ceramsite are 220mm and 620mm respectively, indicating that its fluidity is relatively poor. The ceramsite (PW) pre-wetted for 1 hour significantly improves the fluidity of concrete, and the slump and expansion reach 290mm and 740mm respectively. The use of different proportions of fly ash and mineral powder in composite cementitious materials has little effect on the working performance of concrete. The slump of the composite cementitious materials using 20% fly ash (FA-2) and 30% mineral powder (SG-3) is 280mm, and the expansion is similar. Compared with the untreated group, the slump is significantly improved.
[0073] After the mixture performance test, 100mm×100mm×100mm cubic specimens were formed, and each group contained 12 specimens. The specimens were cured in a standard curing room under the curing conditions of 20℃±2℃ and humidity not less than 95%. The compressive strength and splitting tensile strength of the cube were measured at 7d and 28d. Figure 4 , respectively showing the compressive strength and splitting tensile strength of coal gangue ceramsite concrete with different ash coating treatment methods at 7 days and 28 days. Figure 4 It can be seen that the 28-day compressive strength of the FA-2 group reached the highest value, reaching 45.6MPa, which is 111% of the untreated group, and the splitting strength is close to 3MPa. Compared with the pre-wetted group, the ash-coated groups showed significantly improved 7d compressive and splitting strengths. Overall, the 28d compressive and splitting strength of the FA group mixed with fly ash in the ash-coated composite cementitious material is better than that of the SG group mixed with mineral powder. The above work and mechanical properties tests show that the ash-coated ceramsite concrete has similar slump and expansion as the pre-wetted ceramsite concrete, and has better mechanical properties.
[0074] Table 1 Coal gangue ceramsite concrete mix proportion and mixture properties
[0075]
[0076] Note: Blank refers to the control group using untreated expanded clay; PW refers to expanded clay that was pre-wetted for 1 hour; "FA-1" refers to expanded clay that was coated with fly ash at a content of 10% of the composite cementitious material; "SG-1" refers to expanded clay that was coated with fly ash at a content of 10% of the composite cementitious material.
[0077] Embodiment 4:
[0078] The Blank, PW, FA-2, and SG-3 mixes in Example 3 were selected to form standard specimens of 100mm×100mm×400mm. When the specimens were cured in the standard curing room to the age of 24 days, the specimens for freeze-thaw test were taken out from the curing site in advance, and then the freeze-thaw specimens were immersed in (20±2)℃ water. During immersion, the water surface was (20-30)mm higher than the top surface of the specimens. After curing in water for 4 days, the specimens were placed in a freeze-thaw box at the age of 28 days to start the rapid freeze-thaw test. According to GB / T 50082-2009 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete", the relative dynamic elastic modulus and mass loss rate were tested as shown in Table 2 and Table 3. The appearance of the concrete specimens after 100 freeze-thaw cycles is as follows: Figure 5 . Combining Table 2 and Table 3 Figure 5It can be seen that in 100 rapid freeze-thaw cycles: the concrete specimen (PW) prepared with pre-wetted expanded clay has the largest dynamic elastic modulus and mass loss, and the concrete specimen prepared with ash-coated expanded clay has better antifreeze performance than the concrete specimen prepared with hydrophobic treatment.
[0079] Table 2 Relative dynamic elastic modulus of gangue ceramsite concrete after 100 rapid freeze-thaw cycles
[0080]
[0081] Table 3 Mass loss rate of gangue ceramsite concrete after 100 rapid freeze-thaw cycles
[0082]
[0083] The fly ash, mineral powder and silica fume added to the surface-coated ceramsite coating layer undergo secondary reactions during the hydration process, generating more CSH gel with cement hydration products (calcium hydroxide), which greatly improves the strength of the coating layer and the matrix. At the same time, the coating layer in the cross-sectional transition zone provides a "gradient transition" mechanical structure, which gradually transitions from the strength of the ceramsite to the cement matrix, avoiding the existence of the weak interface transition zone (ITZ), thereby improving the overall compressive strength. In addition, the gangue ceramsite has a certain water absorption capacity, and the water absorption rate is moderately reduced and uniformed after the surface coating. During the hardening process of concrete, the coated ceramsite gradually releases water, alleviates the self-drying phenomenon inside the matrix, promotes cement hydration and secondary reactions of admixtures, and further enhances the strength of the matrix. In addition, the surface coating treatment makes the water absorption rate of the ceramsite tend to be consistent, avoiding the problem of uneven local water-cement ratio of concrete caused by the difference in water absorption capacity of different ceramsites, and improving the consistency of the overall concrete performance.
[0084] The surface-coated coal gangue ceramsite concrete prepared in this application is widely used in various engineering fields due to its light weight, high strength, good durability, and no stratification and segregation. In building structures, it can be used for high-rise buildings, bridge components, and prefabricated components; in infrastructure, it is suitable for roadbeds, culvert pipes, and retaining walls. Its excellent frost resistance makes it perform well in marine engineering such as docks and wave-breaking walls; in industrial buildings, it is suitable for wear-resistant floors and anti-corrosion components of chemical plants.
Claims
1. A method for preparing surface-coated coal gangue ceramsite concrete, characterized in that: The steps include: Step 1: Prepare composite cementitious materials with cement, fly ash or mineral powder and silica fume, and stir them with a mixer until they are evenly mixed; Step 2: quantitatively weigh the composite cementitious material and coal gangue ceramsite obtained in step 1; Step 3: Pour the ceramsite weighed in step 3 into a granulator, start the granulator, add the composite gelling material weighed in step 2 three times, and use a spray pot to spray 1 / 3 of the total water consumption on the ceramsite each time the composite gelling material is added to obtain ceramsite after ash coating; Step 4: curing the ceramsite after the ash coating treatment; Step 5: Use the ash-coated coal gangue expanded clay to completely replace the coarse aggregate to prepare coal gangue expanded clay concrete.
2. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 1, the cement used is ordinary Portland cement, the fly ash is Class II fly ash, and the silica fume is SF96 silica fume; the composite cementitious material is prepared according to the ratio of 6 to 8 parts of cement, 1 to 3 parts of fly ash or mineral powder, and 1 part of silica fume, and stirred for 2 to 3 minutes using a mixer.
3. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 1, characterized in that: In the step 2, the mixture is prepared in a ratio of 1 part of the composite cementitious material to 1.5 to 4.5 parts of the coal gangue ceramsite.
4. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 3, the rotation speed of the granulator used is 25 r / min, and the maximum mass of ceramsite that can be processed each time is 2.4 kg, wherein the total water consumption is calculated based on 50 g of water per 1 kg of ceramsite.
5. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 1, characterized in that: In step 4, the mixture is placed in a standard curing room with a temperature of 20±2° C. and a humidity of more than 95% for 3 days of curing.
6. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 1, characterized in that: In the step 5, the LC30 gangue ceramsite concrete is prepared by mixing the gangue ceramsite, cement, fly ash and fine aggregate after ash coating treatment; In the step 5, the ash-coated coal gangue ceramsite concrete material includes the following raw materials in parts by weight: 352 parts of cement, 88 parts of fly ash, 660 parts of natural river sand, 560 parts of coal gangue ceramsite treated by ash-coated impregnation, 145 parts of water, and 2.2 parts of polycarboxylic acid water reducer; The compressive strength of the cube of the ash-coated coal gangue ceramsite concrete meets the strength design requirement of LC30 lightweight aggregate concrete.
7. The method for preparing surface-coated coal gangue ceramsite concrete according to claim 6, characterized in that: The preparation of coal gangue ceramsite concrete comprises the following steps: mixing surface-coated ceramsite, natural river sand, cement, fly ash and water reducing agent according to a preset ratio, stirring for 30 seconds, then adding water, stirring for 3 minutes, and obtaining the surface-coated ceramsite concrete; The vibration time of the surface coated ceramsite concrete during molding should not exceed 5s.
8. The surface-coated coal gangue ceramsite concrete prepared by the method according to any one of claims 1 to 7, characterized in that: The ash coating layer of coal gangue ceramsite has CSH gel, and the ash coating layer in the interface transition zone between the ceramsite and the cement matrix provides a "gradient transition" mechanical structure, avoiding the existence of a weak interface transition zone (ITZ); After the surface is coated with ash, a 1mm silicate shell is formed; the silicate shell moderately reduces and evens out the water absorption of ceramsite, thus improving the consistency of concrete performance; During the concrete hardening process, the moisture absorbed by the lime-coated expanded clay during the mixing stage is gradually released through some capillary pores on the surface, alleviating the self-shrinkage phenomenon inside the matrix, promoting cement hydration and secondary reactions of admixtures, and enhancing the strength of the matrix.
9. Application of surface-coated coal gangue ceramsite concrete prepared by the method according to any one of claims 1 to 7, characterized in that: The surface-coated coal gangue ceramsite concrete is suitable for various engineering fields; In building structures, it is used in high-rise buildings, bridge components and prefabricated components; In infrastructure, it is used in road subgrades, culvert pipes and retaining walls; In marine engineering, it is used in docks and wave-breaking walls; In industrial buildings, it is used for wear-resistant floors and anti-corrosion components in chemical plants.
Citation Information
Patent Citations
Building ceramsite and preparation method thereof
CN103011707A
Self-insulation-wall ceramsite concrete and preparation method thereof
CN107235681A
Gangue comprehensive integrated utilization method
CN109133683A
Core-shell type sulphoaluminate cement-based high-strength lightweight aggregate and preparation method thereof
CN110526609A
Multi-scale fiber composite reinforced coal gangue ceramsite concrete and preparation method thereof
CN114276075A